New Variety Class of Solitons Arising From the (3+1)-Dimensional Evolution Equation - Zahran, Emad H. M.; Ertaş, Ali Gökhan (European Journal of Applied Sciences, 2025)
Our current work aimed constructing new variety soliton solutions to the completely integrable evolution (3+1)-dimensional nonlinear equation. The suggested model has strong relation with many equations especially with the Korteweg–De Vries (KDV) equation; it describes the real features in several branches of science as physics, fluid, engineering and technology. These soliton solutions of this model will be constructed for the first time using three distinct methods. The three employed methods are the generalized Kudryashov method (GKM), the extended direct algebraic method (EDAM) and (G'/G)-expansion method. The soliton solutions we obtained are novel compared to those previously reported by other authors using different methods.